Exploring multiple-cumulative trapping solid-phase microextraction coupled to gas chromatography–mass spectrometry for quality and authenticity assessment of olive oil. (30th July 2022) - Spadafora, Natasha D.; Mascrez, Steven; McGregor, Laura; Purcaro, Giorgia
Highlights: Use of Multiple-Cumulative Trapping HS-SPME for volatile analysis. Successful quality discrimination of virgin olive oil in commercial categories. Successful geographical origin discrimination of extra virgin olive oil. Abstract: This study explores the potential of an innovative multi-cumulative trapping headspace solid-phase microextraction approach coupled with untargeted data analysis to enhance the information provided by aroma profiling of virgin olive oil. Sixty-nine samples of different olive oil commercial categories (extra-virgin, virgin and lampante oil) and different geographical origins were analysed using this novel workflow. The results from each sample were aligned and compared using for the first time a tile-based approach to enable the mining of all of the raw data within the chemometrics platform without any pre-processing methods. The data matrix obtained allowed the extraction of multiple-level information from the volatile profile of the samples. Not only was it possible to classify the samples within the commercial category that they belonged to, but the same data also provided interesting information regarding the geographical origin of the extra-virgin olive oil.